Numerical Investigation of Fracture Network Formation under Multiple Wells. (20th August 2020) - Men, Xiaoxi; Li, Jiren
Abstract : A two-step fracturing method is proposed to investigate the hydraulic fracture evolution behavior and the process of complex fracture network formation under multiple wells. Simulations are conducted with Rock Failure Process Analysis code. Heterogeneity and permeability of the rocks are considered in this study. In Step 1, the influence of an asymmetric pressure gradient on the fracture evolution is simulated, and an artificial structural plane is formed. The simulation results reflect the macroscopic fracture evolution induced by mesoscopic failure; these results agree well with the characteristics of the experiments. Step 2, which is based on the first step, investigates the influence of preexisting fractures (i.e., artificial structural planes) on the subsequent fracturing behavior. The simulation results are supported by mechanics analysis. Results indicated that the fracture evolution is influenced by pressure magnitude on a local scale around the fracture tip and by the orientation and distribution of pore pressure on a global scale. The constant pressure in wellbore H 2 can affect fracture propagation by changing the water flow direction, and the hydraulic fractures will propagate to the direction of higher local pore pressure. Furthermore, the artificial structural planes influence the stress distribution surrounding the wellbores and the hydraulic fracture evolution by altering the induced stresses around the preexisting fractures. Finally, fracture network is formed among the artificial structural planes and hydraulic fractures when multiple wells are fractured successively. This study provides valuable guidance to unconventional reservoir reconstruction designs.